2021
DOI: 10.5007/2175-8069.2021.e71102
|View full text |Cite
|
Sign up to set email alerts
|

Gerenciamento por decisões operacionais: alternativa para evitar reportar prejuízos

Abstract: O objetivo desse trabalho foi verificar se as empresas brasileiras listadas na Brasil, Bolsa, Balcão [B]3 utilizaram-se do gerenciamento de resultados por atividades reais para evitar reportar prejuízos. A amostra é composta por 157 empresas brasileiras de capital aberto, somando 1570 observações no período de 2008 a 2017. Utilizou-se o modelo de Roychowdhury (2006) para mensurar o gerenciamento de resultados. Para a análise dos dados, utilizaram-se os modelos de regressão linear múltipla. Quanto aos resultado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…of results (Pereira, 2017, França, 2018. Pereira and Tavares (2021) stated that there are several factors that support and show that DTA can demonstrate information about the quality of earnings and, in their studies, they showed that, for company-years with large differences in DTA, it is less persistent in future profits than for firm-years with small DTA differences. Zanon and Dantas (2020) showed in their studies that companies with a high volume (low volume) of DTA stock have a large Contextus -Contemporary Journal of Economics and Management (2024), 22, e91530 | (small) effect on earnings persistence and can be used as a proxy for earnings quality.…”
Section: Dta and Development Of Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…of results (Pereira, 2017, França, 2018. Pereira and Tavares (2021) stated that there are several factors that support and show that DTA can demonstrate information about the quality of earnings and, in their studies, they showed that, for company-years with large differences in DTA, it is less persistent in future profits than for firm-years with small DTA differences. Zanon and Dantas (2020) showed in their studies that companies with a high volume (low volume) of DTA stock have a large Contextus -Contemporary Journal of Economics and Management (2024), 22, e91530 | (small) effect on earnings persistence and can be used as a proxy for earnings quality.…”
Section: Dta and Development Of Hypothesesmentioning
confidence: 99%
“…The Provision for Doubtful Credit (ΔPDCt-1) reflects an increase or reduction in bank profitability, expecting a positive coefficient, because, when the bank grants credit, its profitability is realized through the receipt of loans plus interest, however, when there is an increase in PDC, which means that profit will be provisioned in a future period, being a management variable to signal the current reduction in profit (Kanagaretnam, Krishnan, & Lobo, 2010). While the operating cost (CUSTOOPit) reflects the cost management capacity, reducing banks' profitability and, therefore, the coefficient is expected to be negative (Batten & Vo, 2019, Pereira & Tavares, 2021.…”
Section: Profit Persistencementioning
confidence: 99%
See 2 more Smart Citations